Evolutionary patterns in the geographic range size of Atlantic Forest plants. Issue 10 (17th July 2020) - Leão, Tarciso C. C.; Lughadha, Eimear Nic; Reich, Peter B.
Abstract : Species' geographic range size is arguably the single most important predictor of vulnerability to extinction and a key metric in ecology. Despite this, patterns of specific variation in range size and their underlying reasons are still poorly understood. For example, hypotheses on how evolutionary history affects range size have scarcely been tested. To address these questions, we focused on Brazil's Atlantic Forest flora, one of the most species‐rich in the world, relatively well‐known and highly threatened. We investigated whether and how lineages' diversification rate, number of species and age are associated with species' geographic range size. We estimated the extent of occurrence and area of occupancy of each of 13 283 plant species native to the Atlantic Forest region based on over 500 000 unique records. We used phylogenetic least squares and logistic regressions to analyze how the predictors affect the geographic range size. On average, the higher the diversification rate and number of species in the lineage, the smaller the species range size and the higher the proportion of species with vulnerably small range size. Lineage age showed no clear effect on average range size. The results support our expectations that dynamics of diversification and taxonomic richness considerably affect the species range size. Finally, this work reveals poorly known patterns of range size variation and some of the mechanisms driving variation in range size and vulnerability to extinction.